PENEGAKAN HUKUM TERHADAP ANAK PELAKU TINDAK PIDANA PENGANIAYAAN SEBAGAI ANGGOTA GENG MOTOR ATAU GENGSTER - Monika Karuniasari; Eko Wahyudi (Ekasakti Jurnal Penelitian dan Pengabdian, 2024)
Criminal acts committed by motorbike gangs or gangsters which are common in big cities such as Surabaya include abuse, brawls, and even causing victims. Which makes residents anxious due to their actions. Therefore, this research is important to carry out considering the many cases of abuse committed by underage motorbike gang members which have a negative impact on society, especially in the city of Surabaya. The research method used is a type of empirical legal research obtained from field studies, data sources are primary, secondary and library data, data collection techniques are by means of field research, namely by conducting interviews, documentation, observation. The results of the research show that there are several causes of crimes committed by motorbike gangs or gangsters in the jurisdiction of the Surabaya Police, namely, group warfare, low level of education, social environment and lack of attention from parents. Efforts to overcome motorcycle gang crime include preventive efforts carried out by the police, non-governmental organizations and community leaders, and repressive efforts carried out by the police.